2483. Twelve-Month Immunogenicity and Safety of an Adjuvanted Recombinant Zoster Vaccine in Immunosuppressed Adults Post Renal Transplant: a Phase III Randomized Clinical Trial. (26th November 2018) - Vink, Peter; Torrell, Josep Maria Ramon; Sanchez-Fructuoso, Ana I; Kim, Sung-Joo; Kim, Sang Il; Zaltzman, Jeffrey; Ortiz, Fernanda; Plana, Josep Maria Campistol; Rodriguez, Ana Maria Fernandez; Rodrigo, Henar Rebollo; Marti, Magda Campins; Perez, Rafael; et al.
Abstract: Background: The efficacy of the non-live adjuvanted recombinant zoster vaccine (RZV, containing a truncated form of varicella-zoster glycoprotein E [gE] and Adjuvant System AS01B ) is >90% in adults ≥50 years of age (YOA) (ZOE-50/70) and >68% in hematopoietic stem cell transplant recipients ≥18 YOA (ZOE-HSCT). 1 This study (NCT02058589) evaluated immunogenicity and safety of RZV in renal transplant recipients ≥18 YOA receiving immunosuppressive therapy. Previously unreported reactogenicity and 12-month post-last dose safety and immune persistence data are presented. Methods: In this phase III, 1:1 randomized, observer-blind, multicenter trial, patients received 2 doses of RZV or placebo. gE-specific immune responses were assessed at 1 (M2) and 12 (M13) months post-dose 2: humoral immunity by vaccine response rate (VRR) and geometric mean antibody concentration (GMC), and cell-mediated immunity (CMI) by VRR and CD4 + T-cell frequency. Solicited general and unsolicited adverse events (AEs) were collected 7 days pre-dose 1 as a within-participant control. Solicited and unsolicited AEs were also recorded for 7 and 30 days after each dose, respectively. Serious AEs (SAE) and potential immune-mediated diseases (pIMDs) were recorded up to study end (M13). Results: Humoral and CMI in the RZV group persisted through M13 appearing higher in the RZV group vs. placebo (Table 1). The frequency of solicited local AEs and of general AEs myalgia and fever was higher in the RZV group vs. placebo and balanced between study groups for the other general AEs, pIMDs and SAEs (including allograft rejections) (Table 2, Figure 1). No concerns regarding renal function were reported. Suspected HZ cases were recorded among 2 RZV and 6 placebo recipients. In the RZV group, within-participant pre- and post-vaccination solicited general AEs were reported at similar rates for fatigue, gastrointestinal symptoms and headache, and higher rates post-vaccination for myalgia, shivering, and fever (Figure 1). Conclusion: RZV was highly immunogenic, eliciting robust humoral and CMI that persisted up to 12 months in adult renal transplant recipients. No safety concerns were identified over a 1-year follow-up. Reference 1. de la Serna, BMT Tandem Meeting 2018, abs LBA2. Funding: GlaxoSmithKline Biologicals SA Disclosures: P. Vink, GSK group of companies: Employee and Shareholder, Salary and stock shares. S. J. Kim, GSK group of companies: Investigator, Research grant and Research support. M. Campins Marti, GSK group of companies: Consultant, Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Research grant and Speaker honorarium. D. Kumar, GSK group of companies: Scientific Advisor, Consulting fee. K. Doucette, GSK group of companies: Investigator, Research support. S. A. McNeil, GSK group of companies: Grant Investigator, Research grant and Research support. L. Campora, GSK group of companies: Employee and Shareholder, Salary. E. Di Paolo, GSK group of companies: Employee, Salary. M. El Idrissi, GSK group of companies: Employee, Salary. M. López-Fauqued, GSK group of companies: Employee, Salary. B. Salaun, GSK group of companies: Employee and Shareholder, Salary. T. Heineman, GSK group of companies: Consultant, Employee and Shareholder, Consulting fee and Salary. L. Oostvogels, GSK group of companies: Employee, Salary and stock and stock option.